The Relevance of Clausewitz’s Theory with Fourth Generation Warfare in the Context of Asymmetrical Wars - Dirgantara, Hizkia Dicken; Priyanto, Priyanto (PT FORMOSA CENDEKIA GLOBAL, 2025)
This article explores the relevance of Clausewitz's theory of warfare with the concept of Fourth Generation Warfare (4GW) in the context of asymmetrical wars. Clausewitz, in his work On War, focuses on war as a continuation of politics by other means, while 4GW introduces a more complex approach involving non-state actors, asymmetrical tactics, and blurred political goals. This study employs a descriptive qualitative method with a literature review approach to analyze how Clausewitz's theory remains significant in understanding modern conflicts characterized by the dynamics of fourth-generation warfare. Through the analysis of literature on 4GW and Clausewitz's theory, this paper aims to reveal the connection between traditional strategies and contemporary challenges, and how military doctrines can be adapted to asymmetrical warfare contexts.